2021
DOI: 10.3390/su13074060
|View full text |Cite
|
Sign up to set email alerts
|

Empathic Design in Engineering Education and Practice: An Approach for Achieving Inclusive and Effective Community Resilience

Abstract: In this paper, we argue that an inclusive and effective community resilience approach requires empathy as a missing component in the current engineering education and practice. An inclusive and effective community resilience approach needs to be human-centric, individual- and communal-sensitive, justice-oriented, and values-based consistent. In this paper, we argue that three kinds of empathy, namely cognitive, affective, and conative, play a central role in creating and sustaining an inclusive and effective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Researchers have previously suggested that to establish community awareness, ideologies, and actions aimed at social justice, all three components of empathy are needed. 2 In this research, Zaki's framework served as the lens that informed our research questions, protocol development, analysis, and the interpretation of the results. Below, we describe each component separately as well as the role they play in cultural development, understanding, and communication.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Researchers have previously suggested that to establish community awareness, ideologies, and actions aimed at social justice, all three components of empathy are needed. 2 In this research, Zaki's framework served as the lens that informed our research questions, protocol development, analysis, and the interpretation of the results. Below, we describe each component separately as well as the role they play in cultural development, understanding, and communication.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…At the societal level, empathy has been highlighted as an essential fabric to a civil society with collective resilience (de Waal, 2009), especially in traumatic events (Afroogh et al, 2021; Taylor et al, 2020) due to the well-established corresponding relationship between empathy and prosocial behaviors (Bohns & Flynn, 2021). High empathy levels, for instance, could positively predict altruistic responses and prosocial behaviors to others, which in turn foster prosocial moral reasoning (Paciello et al, 2013).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Thus, perceived social support has been found a positive contributor to collective resilience, especially in public crises. It is well supported that social support not only enhances individual resilience (Afroogh et al, 2021; Taylor et al, 2020) but also helps individuals to remain empathetic to each other in difficult times (Park et al, 2015).…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…The size of the required subsidy is remarkably small and well within reach of individual countries, or even companies that would stand to benefit from the existence of air capture technology, or private foundations that choose to develop a solution to the climate problem and sustainable energy systems. 98,99 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: ■ Conclusionmentioning
confidence: 99%